Implementation of the Multiple Intelligence Approach in Qur'anic Memorization Learning: Analysis of Strategies and Students Social Interaction Patterns - Rangkuti, Charles; Ependi, Rustam; Tumiran, Tumiran; Rahma, Riza (Fitrah: Journal of Islamic Education, 2024)
Memorizing the Qur'an often faces challenges related to the diversity of students' learning styles. Each individual has a different way of learning, which is caused by differences in intelligence types. Therefore, an approach that accommodates this diversity of intelligence is important in learning, one of which is the Multiple Intelligences approach developed by Howard Gardner. This approach emphasizes that every individual possesses various types of intelligence that can be optimized, such as linguistic intelligence, musical intelligence, interpersonal intelligence, and intrapersonal intelligence. This study aims to analyze the implementation of the Multiple Intelligences approach in Qur'an memorization learning, focusing on the potential application, strategies, and challenges faced in its implementation. The method used is a qualitative case study approach, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the application of learning strategies tailored to students' dominant intelligences has a positive impact on improving Quran memorization. The implications of this study suggest that the Multiple Intelligences approach can enhance Quran memorization outcomes and students' learning motivation, consistent with Howard Gardner's theory of Multiple Intelligences.